Comparative synphysiological studies on Brachypodium pinnatum dominated forest- and steppe-type grasslands - Fóti, Szilvia (Acta Biologica Szegediensis, 2002)
The lack of community-level, synphysiological investigations inspired us to plan a study on Brachypodium pinnatum grasslands, well-known objects of local long-term coenological and dynamical examinations in Hungary. After removing every species but B. pinnatum, CO2 gas exchange responses by the grass stands indicated the difference in the degree of water-stress between the two investigated habitats. However, in intact community measurements these responses are masked by the presence of other species, by the change of species coexistence patterns and by different light conditions. We conclude that to understand the physiological performance of a dominant species in a plant community and also the photosynthetic behaviour of the whole community, considering the coenological aspect and examining the intensity of photosynthesis at a level of organization higher than the population level are essential.